Enforcement of ECtHR Judgments and respect of the principle of res judicata in civil matters in Italy - Grassi, Michele (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
While the Italian legal system has long provided for the possibility of removing the prejudicial effects of criminal law decisions adopted in violation of human rights, the introduction of a ground for revoking a civil judgment for contravention of the ECHR is more recent. Nonetheless, the new revocation mechanism has a particularly narrow scope of application, so that, in many cases, it is still not possible to reopen national proceedings even though a ruling from the European Court of Human Rights (ECtHR) has finally established the incompatibility of the civil judgment in question with the human rights protected by the ECHR. This study investigates the possible existence of an obligation to reopen domestic civil proceedings as a consequence of the obligation to abide by the judgments of the ECtHR under Article 46 ECHR, considered in light of the rules on State responsibility for international wrongful acts.
Keywords: Civil judgment contrary to the ECHR; revision of judgment; enforcement of ECtHR judgments; Article 46 ECHR; State responsibility for international wrongful acts; Obligation to make reparation; restitutio in integrum